Real-time condition assessment of a painted megalithic cave using Wireless Sensor Network. (February 2022) - Wang, Chao; Tavares, Alice; Fonseca, Jorge; Soares, Filipe; Li, Zili
Highlights: Wireless sensor network to assess dolmen structural performance for the first time. Barely-seen structural stability analyses performed for the self-supporting dolmen. Scarcely-investigated visitation effect on dolmen interior microclimate analysed. Mechanisms of dolmen painting deterioration caused by visitations addressed. Advice on enhancing structural robustness and environmental resilience proposed. Abstract: The deterioration of underground heritage caves caused by visitations has attracted extensive attention over the recent decades. Most previous research focused on investigating the impact of visitors on the microclimatic conditions of the interior of large show caves, but much less relevant effort was made for small confined caves, for example, megalithic burial dolmen caves. In addition to environmental condition issues, the structural performance of underground heritage caves also deteriorates in the long-term subject to both natural hazards (e.g. creep in geo-materials and extreme weather) and manmade ones (e.g. construction activities). To this end, a real-time Wireless Sensor Network (WSN) system is deployed inside an underground megalithic dolmen to monitor its structural performance with time so as to assess its long-term structural stability. Meanwhile, the WSN system together with other field sensors and inspection monitors the interior environmental change caused by human visitation effect, aiming to reveal the mechanism behind visitor-caused rock painting deterioration in the small confined dolmen chamber. Results show that structurally, the dolmen can be regarded as generally stable despite a progressive development of structural performance during the first 1.5 months and accidental instability of the near-opening pillar A. In terms of environmental condition, the presence of visitors leads to significant changes of interior microclimatic conditions frequently inside the confined cave against consistent rock painting conservation. Particularly, the cave paintings may deteriorate critically with time as visitation induces a 'hotbed' environment for interactions between microorganisms and microstructures of the rock paintings due to the variations of interior microclimate. To ensure long-term structural stability and restore acceptable level of interior microclimate, tinted hydraulic lime and steel rod/brace were recommended for enhancing structural robustness and a mechanical ventilation system for improving environmental resilience of the dolmen. A generalized monitoring approach was proposed for the reference of other similar caves.